Central habituation and distraction alter C‐fibre‐mediated laser‐evoked potential amplitudes. (15th June 2015) - Hüllemann, P.; Shao, Y.Q.; Manthey, G.; Binder, A.; Baron, R.
Abstract: Background: Recent studies applied laser‐evoked potentials (LEP) for the analysis of small nerve fibre function and focused on the detection of stable C‐fibre‐mediated potentials (C‐LEPs); high technical requirements were needed. The diagnostic significance is still controversially discussed. So far, only few studies focused on the susceptibility of C‐LEPs to distraction and other influences. We hypothesized that C‐LEPs are altered by habituation processes and distraction. Methods: Twelve subjects were tested with a C‐fibre laser set‐up (neodymium:yttrium‐aluminium‐perovskite laser with a 10‐mm beam diameter and 10‐ms stimulus time) at the left perioral area. In condition I, the subjects received repetitive painful laser stimuli at the right hand to induce habituation. In condition II, the subjects had to fulfil an auditory discrimination task (where the subjects had to estimate the pitch of different tones on a scale for 20 min). C‐LEPs were retrieved before and after the habituation or distraction paradigm. C‐LEPs were also measured in a control group who was not influenced by laser stimuli or other disturbances during a 23‐min break between the two test sessions. Results: In both test conditions, there was significant C‐LEP amplitude reduction. The LEP amplitudes of the control group remained unchanged. Conclusions: In the approach of detecting C‐fibre‐mediated potentials with LEP, future studies should take the high susceptibility to distraction and habituation into account.